2021
DOI: 10.3389/fmed.2021.698242
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications of Veno-Arterial Extracorporeal Membrane Oxygenation: A Retrospective Case-Control Study

Abstract: Background: To explore the epidemiology, clinical features, risk indicators, and long-term outcomes of neurological complications caused by veno-arterial extracorporeal membrane oxygenation (V-A ECMO).Methods: We retrospectively analyzed 60 adult patients who underwent V-A ECMO support in our unit from February 2012 to August 2020. These patients were separated into the neurological complications group (NC group) and the non-neurological complications group (nNC group). The differences in basic data and ECMO d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…We found that after controlling for a high initial Pa CO 2 , within the VV ECMO group, the early relative ΔCO 2 decrease was associated with neurologic complications. These findings have strong physiological basis as detailed previously, and similar relationships have been shown in smaller studies (19–26). Finally, within this pediatric cohort, mortality increased with those who had a relative ΔCO 2 decrease over 30%.…”
Section: Discussionsupporting
confidence: 89%
“…We found that after controlling for a high initial Pa CO 2 , within the VV ECMO group, the early relative ΔCO 2 decrease was associated with neurologic complications. These findings have strong physiological basis as detailed previously, and similar relationships have been shown in smaller studies (19–26). Finally, within this pediatric cohort, mortality increased with those who had a relative ΔCO 2 decrease over 30%.…”
Section: Discussionsupporting
confidence: 89%
“…In our previous study, 65% of VA-ECMO-supported patients suffered neurological complications, and the identification of neurological complications mainly relied on subjective assessment methods such as GCS, CPC score, confusion assessment method for the ICU (CAM-ICU), and neuroimaging examination ( 11 ). To more accurately identify the neurological damage in ECMO-supported patients, we established the MNM-guided protocol, which is based on bedside noninvasive techniques such as qEEG, NIRS, and TCCD, combined with GCS and neurological examination, guiding clinicians to optimize the management of VA-ECMO patients.…”
Section: Discussionmentioning
confidence: 99%
“…We hope to conveniently monitor the resistance of cerebrovascular, cerebral blood flow velocity, and even whether there is cerebral vasospasm, cerebral edema, cerebral hemorrhage, brain midline shift, etc. We found that continuous non-pulsatile perfusion (NP) >12 h was an independent risk indicator for neurological complications in VA-ECMO-supported patients ( 11 ). TCCD is a noninvasive test that uses ultrasonography to estimate CBF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurologic complications occur during or immediately after ECMO and are associated with poor survival [ 4 , 5 , 6 ]. Acute ischemic stroke, intracranial hemorrhage, seizures, cognitive decline, and brain death are a few of the short-term complications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%